Strategic Planning Practices and Challenges: The Case of SMEs in Macedonia - Hristova, Snezhana; Bundaleska , Elena (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
Strategic planning is an important element for companies growth, gaining competitive advantage as well as further development. However, not many scholars have done researches which emphasize the role of strategic planning in small and medium-sized enterprises (SMEs). In Macedonia, SMEs are the major source of the country’s potential economic-growth in terms of their contribution toward the creation of employment and overall economic development. This study is about to find out whether and how strategic planning is employed in the Macedonian SMEs, as well as to explore the main characteristics of the strategic planning process. Data was gathered using online questionnaire method and analyzed with standard tools of descriptive statistics. It aims to work as a reference for the business owners and manager to better improve and utilize the strategic planning tools for their future growth.
Keywords: strategic planning; SMEs; competitive advantage